PERANCANGAN FORMULIR ELEKTRONIK DIENKRIPSI DENGAN METODE BLOWFISH PADA SISTEM PENDAFTARAN ONLINE (STUDI KASUS : SELEKSI MANDIRI UNIVERSITAS TANJUNGPURA) - Kurniawan, Ferry (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Seleksi Mandiri Tanjungpura University is one of the entrance method to the college, especially in the TanjungpuraUniversity. Registration of Seleksi Mandiri Tanjungpura University done directly by the candidates of the student. This existing method takes quite a long time. The number of applicants is not proportional to the number of committees that serve and verify the administrative requirements of participants, so this resulted in a queue ofstudent candidates. Online system that used as a service in the registration system have been widely applied in daily life. It proved to minimize the problems that previously occurred. Long lines of queue and paper used as a medium of registration can be reduced and prevented with the online service systems. Electronic form is an application that designed for Seleksi Mandiri Tanjungpura Tanjungpura University registration system. Application form fulfillment will be possible to conduct in conditions of a computer connected or not connected to the Internet. However it can be done at offline. One method to protect data from unwanted party is to randomize the data sent, so if the data is received by the other party, they do not understand the purpose of the data. Blowfish algorithm is an algorithm which is quite good and applicable. Blowfish have varying levels of security, the key length used by Blowfish may vary by the system. The application uses data snap technology by applying service application so it becomes more secure because of the indirect communications with the back end. The results show that the design and testing of these applications can be used for the registration process. Prospective participants will receive a registration receipt cards used to take exams.Â